Rehabilitation and Disability Spectrum From Adverse Childhood Experience: The Impact of the Movement Cognition and Narration of Emotions Treatment (MCNT) Version 2.0 - Baglio, Gisella; Zanette, Michela; Di Cesare, Monica; Di Tella, Sonia; Clerici, Mario; Baglio, Francesca; Blasi, Valeria (Frontiers in Psychiatry, 2021)
Adverse Childhood Experiences (ACE) are associated with an increased risk of cerebral, behavioral, and cognitive outcomes, and vulnerability to develop a Borderline Intellectual Functioning (BIF). BIF is characterized by an intelligence quotient (IQ) in the range 70-85, poor executive functioning, difficulties in emotion processing and motor competencies. All these difficulties can lead to mental and/or neurodevelopmental disorders that require long-term care. Accordingly, we developed an intensive and multidomain rehabilitation program for children with ACE and BIF, termed the Movement Cognition and Narration of emotions Treatment (MCNT1.0). The efficacy of MCNT1.0 on cognitive and social functioning was demonstrated with a previously reported randomized controlled trial (RCT). To extend the impact of the treatment also to the motor domain a new version, called MCNT2.0, was implemented. The present study aims to verify the feasibility of MCNT2.0 and its effects on the motor domain. A quasi-experimental approach was used in which a group of 18 children with ACE and BIF were consecutively recruited and participated in the MCNT 2.0 program. Participants were compared with the MCNT1.0 group as an active comparator, using the dataset of the RCT. The two groups received a full evaluation comprising: the Wechsler Intelligent Scale for Children-IV (WISC-IV), the Movement-ABC (M-ABC), the Test of Gross Motor Development (TGMD), the Social Skills from Vineland Adaptive Behavioral Scale-II (VABS-II) and the Child Behavior Check List 6-18 (CBCL). An ANCOVA was carried out on changes in the scale scores from baseline with age and baseline score as covariates. Results showed a mean adherence to treatment of 0.85 (sd=0.07), with no differences between groups in IQ, and Social Skills changes, while greater improvements for motor abilities were shown in the MCNT 2.0 group: M-ABC (p=0.002), and TGMD (p= 0.002). Finally, greater improvement in the CBCL scale was observed in the MCNT 1.0 group (p=0.002). Results indicate that due to its positive effects on cognitive, social participation and motor domains, MCNT2.0 may represent a protective factor against maladaptive outcomes of children with ACE and BIF.